Exploring U.S. Social Work Students' Sexual Attitudes and Abortion Viewpoints. Issue 6 (24th July 2017) - Begun, Stephanie; Kattari, Shanna K.; McKay, Kimberly; Ramseyer Winter, Virginia; O'Neill, Elizabeth
Abstract : Social workers frequently engage with sexual and reproductive health topics, yet a notable paucity of social work research exists regarding abortion. Informed by overlapping theoretical frameworks of human rights and reproductive justice, this study examined a large, nationwide survey of social work students in the United States ( N = 504). Linear regressions indicated that students' endorsements of permissive sexual attitudes and support for birth control are inversely associated with holding anti-choice abortion views. Moreover, distinct relationships were found among sociodemographic characteristics and abortion attitudes and knowledge, suggesting that social work education efforts regarding contentious reproductive and sexual health topics should also focus on nuances of cultural competence and diversity, as well as general human rights principles and professional ethics.